ENHANCING STEM EDUCATION THROUGH STEM LEADERSHIP PRACTICES: A FUZZY DELPHI METHOD APPROACH - Radhiah Muda; Ahmad Zabidi Abd Razak; Hidayah Mohd Fadzil (MOJES: Malaysian Online Journal of Educational Sciences, 2023)
Using the fuzzy Delphi method, this study aims to obtain expert agreement on the elements of school leaders’ practices that influence student learning and teacher effectiveness in strengthening STEM instructions. An instrument on STEM leadership was presented to a total of 26 experts in STEM-related fields. The results of this study show that the expert panel agreed with the proposed constructs and elements of school leaders’ practices that influence student learning and teacher effectiveness in STEM. The practices tested in the study also met the conditions specified in the fuzzy Delphi method, namely, a threshold value (d) greater than 0.2 (d > 0.2), experts’ agreement greater than 75% with values ranging from 81% to 96% agreement, and a fuzzy score value (A) greater than 0.5 (A ≥ 0.5) with values ranging from 0.865 to 0.918. The defuzzification process used by the fuzzy Delphi method also reorders all items by priority based on expert consensus. Of all the elements agreed upon by the experts, the element that ranked highest in the construct of student learning is related to the leader’s emphasis on hands-on activities through problem-based learning/project-based learning (PBL) in improving student skills. The element that ranks highest in the construct of teacher effectiveness is related to the leader’s ability to promote innovation in teaching to enhance the quality of STEM learning.